OPPORTUNITIES FOR THE DEVELOPMENT OF THE TOURISM SECTOR (American Journal of Business Management, Economics and Banking, 2026)
This article examines the potential for the development of the tourism sector in the Republic of Karakalpakstan. The region’s rich cultural heritage, unique natural landscapes, and traditional festivals offer significant opportunities for growth in eco-tourism, adventure tourism, and cultural tourism. The study identifies key challenges, including underdeveloped infrastructure and limited international awareness, and proposes strategic solutions such as sustainable tourism models, investment attraction, and capacity building among local communities. Through strategic planning and international collaboration, Karakalpakstan can position itself as a distinct and attractive destination on the global tourism map.